Appendix 5.11: Francisco I. Chavez, petitioner, vs. Presidential Commission on Good Government (PCGG) and Magtanggol Gunigundo, (in his capacity as chairman of the PCGG), respondents - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies, 2017)
The compromise agreement mentioned by Raissa Robles is reproduced in full in the decision, along with a supplemental agreement. Assailed were procedural and substantive issues regarding the compromise agreement. One procedural issue—the standing of lawyer Francisco Chavez, who filed as a taxpayer and a citizen—was rendered moot and academic because of the inclusion of the petitioners-in-intervention, who were recognized by the Supreme Court as “legitimate claimants of the Marcos wealth.” Among the substantive issues, the agreement was declared in many ways legally infirm, even unconstitutional. One wonders, however, if the agreement was approved by the president at the time, if the Supreme Court would have ruled differently.